Rainfall Threshold for Roadside Shallow Landslide in Mid-Himalayan Region of Nepal - Neupane, Suresh; Bhandary, Netra Prakash (Journal on Transportation System and Engineering, 2025)
Nepal's road transportation infrastructure is primarily dependent on mountain routes, which are severely disrupted by rainfall induced landslides during the monsoon season.  An early warning system based on a localized rainfall threshold is essential for disaster risk reduction because slope stabilization is expensive and road protection resources are scarce. This study uses intensity-duration methodologies and statistical analysis of historical rainfall data in the Mid-Himalayan region to ascertain the relationship between the occurrence of landslides and important triggering elements, including rainfall.  For the roadside landslide in the Mid-Himalayan region, a local rainfall intensity-duration (I-D) threshold was determined by fitting a power-law equation obtained from 57 landslide events from 2017 to 2024, taking into account lower limitations delineated by quantile regression. The results show that there is a high chance of roadside landslides in the research area starting when there is 1.75 mm of rain per hour for 48 hours.  The findings highlight the significance of cumulative antecedent rainfall in landslides and indicate that extended moderate rainfall (>72 hours) considerably adds to slope destabilization.  The results show that July and August are the most dangerous months for roadside landslides, with the mid-Himalayan range experiencing the most rainfall and the high Himalayas seeing the least.  By integrating this threshold into road infrastructure design and transportation management, authorities may improve disaster preparedness, give timely warnings, and reduce casualties, thereby boosting road network resilience in the mid-Himalaya region.